Trace element and stable isotope dispersion halo around a high sulfidation epithermal Au-Ag deposit emplaced in Quarzitic Sandstone: The Lagunas Norte Deposit, Northern Peru - Cerpa Cornejo, Luis Moroni (2008)
Artículo es parte del número especial: Awards Ceremony Speeches and Abstracts of the 18th Annual V.M. Goldschmidt Conference Vancouver, Canada July, 2008.